The Influence of Quality of Work Life on Job Satisfaction with Organizational Citizenship Behavior as an Intervening Variable - Septias Fajar, Rizky Dwi; Asfiyah, Nurul; Roz, Kenny (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The aim of this research is to determine the influence of quality of work life, job satisfaction, organizational citizenship behavior and whether organizational citizenship behavior is able to act as a link or mediate the influence of quality of work life on job satisfaction of employees at PG installations. Djoekir Jombang. This research was conducted on employees of the PG installation section. Tjoekir Jombang with 58 employees as respondents. The sampling technique in this research used total sampling. The data collection technique in this research was carried out by distributing questionnaires. Data analysis techniques use path analysis, statistical t test, Sobel test and the SPSS 25 program. From the research results it can be concluded quality of work life shows good results, job satisfaction shows satisfied results, organizational citizenship behavior shows high results, quality of work life has a positive and significant effect on job satisfaction, quality of work life has a positive and significant effect on organizational citizenship behavior, organizational citizenship behavior has a positive and significant effect on job satisfaction and organizational citizenship behavior mediates the effect of quality of work life on employee job satisfaction. The higher the organizational citizenship behavior, the greater the influence of quality of work life on job satisfaction.